3-T high-b-value diffusion-weighted MR imaging in hyperacute ischemic stroke - Lettau, Michael; Laible, Mona (Journal of neuroradiology, 2013)
Background and purpose: In patients with hyperacute ischemic stroke, early demonstration of infarction is essential. Diffusion weighted imaging (DWI) is the key method for detecting hyperacute infarction. The value of high b-value DWI in hyperacute ischemic stroke is controversial at 1.5T, and is unknown at 3 T. The aim of this study is to explore the value of high b-value versus standard b-value DWI at 3 T in hyperacute stroke with quantitative and qualitative analysis. Material and methods: This study prospectively included 104 consecutive patients with hyperacute stroke. At 3 T, conventional MR sequences and DWI were performed. The examination included a standard DWI (b=1000 s/mm2) and two high b-value DWI (b=3000 s/mm2 and b=5000 s/mm2). Qualitative and quantitative analysis was performed. Results: With increasing b value, DW images appeared noisier. The number of detected lesions was significantly higher on b=3000 images than on the other DW images and higher on b=5000 images than on b=1000 images. The number of lesions greater than 1 cm was not significantly different. Lesion conspicuity was higher, boundary better seen, lesion extent bigger, and estimation of final infarct size was better on high b-value than on standard b-value DWI. Contrast-to-noise-ratio (CNR) and signal-to-noise-ratio (SNR) decreased and contrast ratio (CR) increased on high b-value DWI compared to standard b-value DWI. Conclusion: At 3 T, high b-value DWI was superior to standard b-value DWI in detection of hyperacute infarction and prediction of final infarct size in spite of increasing imaging artifacts.